Internalisasi Nilai-nilai Islam Wasathiyyah dalam Sistem Pendidikan Pondok Pesantren Tahfizh Ikramul Qur’an Bengkalis - Nadana Mardhotillah; Desi Pajrianti; Khazri Osman; Junaidi Junaidi (MAN 4 Kota Pekanbaru, 2026)
This study investigates the cultivation of Islam Wasathiyah values at Pondok Pesantren Tahfizh Ikramul Qur’an Bengkalis. Addressing the gap between rigid textual memorization and religious moderation, this research aims to analyze the embedded moderate values and describe their internalization process. Utilizing a qualitative descriptive approach with a case study design, data were gathered through deep interviews, observation, and documentation analysis, then evaluated using interactive analysis model. Findings reveal six core values: tawassuth, tawazun, i’tidal, tasamuh, musawah, and syura. The internalization operates through a holistic model integrating national and Islamic curricula, teacher role-modeling (living curriculum), 24-hour boarding habituation with peer mentorship, dialogic HOTS-based instruction, and inclusive preaching practice (muhadharah). This study demonstrates that tahfizh-based education can foster critical, open-minded, and moderate traits. Theoretically, it offers a novel “holistic internalization model based on Qur’anic memorization and boarding habituation” to enrich religious moderation discourse in Islamic boarding schools.